Analysis of cross-chain technology of blockchain - Zhao GUO; Shuaiyin GUO; Shengli ZHANG; Lingyang SONG; Hui WANG (物联网学报)
With the development of blockchain technology,more and more blockchain projects have appeared.Due to the closure property of the blockchain,different blockchains have become islands of value.The information interaction and value transfer problems between different blockchains need to be solved urgently.The cross-chain technology is to solve the cross-chain operation problems of assets and data between different chains.There are many attempts and developments on cross-chain technology in the past few years,and the major models of cross-chain include Hash lock,notary mechanism,side chain and relay technology,etc.The concept of each cross-chain technology was introduced,and the advantages and disadvantages of each cross-chain technology were summarized and analyzed.